Seni Media Baru Di Malaysia (1980an-2018): Analisis Karya-Karya Menerusi Pendekatan Bertema - Mohamad Elham, Siti Khadijah (2020)
This thesis applies qualitative research methodology with a focus on the analysis of the document as a data collection. This thesis examines the works of New Media Art in Malaysia between the 1980s and 2018 from the perspective of strategy and themes. Bearing analysis techniques and contextual content, this thesis frames New Media artworks from two perspectives to identity and culture in the work of Malaysian art artists. Therefore, this thesis considers that the cultural and identity aspects of the New Media Art are still a reference in the composition of a number of artists in Malaysia until today in many ways and perspectives.